2018
DOI: 10.1097/ccm.0000000000002769
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Plus Piperacillin-Tazobactam and Acute Kidney Injury in Adults: A Systematic Review and Meta-Analysis

Abstract: The combination of vancomycin plus piperacillin-tazobactam increased the odds of acute kidney injury over vancomycin monotherapy, vancomycin plus cefepime or carbapenem, and piperacillin-tazobactam monotherapy. Limited data in critically ill patients suggest the odds of acute kidney injury are increased versus vancomycin monotherapy, and mitigated versus the other comparators. Further research in the critically ill population is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(110 citation statements)
references
References 58 publications
2
107
0
1
Order By: Relevance
“…One of the studies evaluated the brief (Ͻ72 h) use of combination therapy in critically ill patients (24). Recent meta-analyses were also unable to adequately assess the interaction of VPT in the critically ill patient population due to a lack of adequate data (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the studies evaluated the brief (Ͻ72 h) use of combination therapy in critically ill patients (24). Recent meta-analyses were also unable to adequately assess the interaction of VPT in the critically ill patient population due to a lack of adequate data (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…ill patient populations, but limited studies in the critically ill population have failed to demonstrate an increased risk of AKI with VPT (14,24,(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…[ 37 ] The analysis we have performed is in agreement with recent reports of piperacilln/tazobactam associations vAKI, which has only been recently identified. [ 38 , 39 ] The strength of the associations of nafcillin and clindamycin with vAKI warrant that the use of nafcillin or clindamycin with vancomycin should be investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed mechanism of the cefepime-associated AKI was interstitial nephritis and direct cytotoxic damage with dose-dependent manner [ 7 , 8 , 9 ]. Although two meta-analyses have showed that piperacillin-tazobactam plus vancomycin led to a higher risk of AKI than cefepime plus vancomycin, the difference was not significant in critically ill patients [ 30 , 31 ]. This finding might reflect that AKI might be substantial depending on the morbidity of the patients and severity of the infection.…”
Section: Discussionmentioning
confidence: 99%